Empowerment of Persons with Disabilities with Blind Jatabek through Tuina Chuzhen Massage Therapy Training - Ony Susita; R.M. Alfian; Willie Japaries; Wijono Sukaputra Agussalim; Hedi Suanto Tjong; Metta Sari; Erni Chrisilia Suhendry; Aditya Prabowo Audisapta; Adrianus Suyadi, S.J.; Anastasia S.P; Dian Susanti; Sutrisno (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
ABSTRACT Background: People with disabilities, especially the blind, are members of society who have limited vision. Therefore, they require specific methods to learn certain skills to earn a living. One such skill suitable for the blind is massage therapy, which can be learned without relying on sight, but relying on the sense of touch. Purpose: This paper aims to describe the experience of training blind people to perform a special massage treatment called Tuina Chuzhen. Methods: The experience of training blind people to perform Tuina Chuzhen massage is described chronologically and systematically from facts and primary data collected during six training sessions at the Daya Dharma Institute of the Archdiocese of Jakarta, with support from traditional Chinese medicine experts from the Nalanda Institute. Main Results: The Tuina Chuzhen massage training for 20 blind people went smoothly during six sessions over a period of one month. The training participants successfully mastered the Tuina Chuzhen method using the provided short wooden rods. Mastery of these skills was evident in the participants' recognition and their ability to pass the competency test conducted by the Nalanda Institute's assessment team after the training. Conclusion: Tuina Chuzhen massage training can bring tangible benefits to the visually impaired. Keywords: Massage, tuina Chuzhen, disability, visual impairment.